The investigation of the growth and perfection of the poly(ethylene terephthalate) crystalline region from amorphous state during annealing using a controlled temperature gradient. Issue 3 (3rd March 2021) - Xu, Duigong; Wang, Hai; Bin, Yuezhen
Abstract: The growth and perfection of the crystalline region during the annealing of amorphous poly(ethylene terephthalate) (PET) was studied systematically using a homemade temperature gradient (T‐gradient) ranging from 50 to 250°C. Double melting peaks were observed from the differential scanning calorimetry (DSC) thermograms when PET film was annealed at the temperatures ( T a ) above the PET crystallization temperature ( T c  ≈ 120°C) with a constant primary melting peak at around 256°C and an increased secondary melting peak on the range of 120 and 250°C. The profound broadening of the wide angle X‐ray diffraction (WAXD) peaks in both transmission and reflection modes indicated that there were a lot of tiny crystals when PET films were annealed between 120 and 200°C, and the shift of the WAXD peaks revealed the presence of the paracrystals in the PET films. The growth and perfection of crystalline region of PET in condition of amorphous and annealed ( T a  = 128°C) PET samples were investigated on the basis of Fourier transform infrared spectra and simultaneous WAXD‐DSC measurement. It was found that the conformational transition of the soft ethylene glycol moiety and rigid phenylene moiety in amorphous PET began at around 120 and 200°C, respectively. The microcrystal sizes in the PET film annealed at 128°C exhibited no change at the time that the secondary melting peak showed up, which meant the secondary melting peak might be attributed to the melting of the paracrystals inside or on the surface of the microcrystals. Abstract : In this article, the growth and perfection of the crystalline region during the annealing of amorphous poly(ethylene terephthalate) (PET) is studied systematically using a homemade temperature gradient (T‐gradient) ranging from 50 to 250°C. The results show that PET paracrystals are distributed on the surface and inside of the PET microcrystal, which is an interpretation of the double melting phenomenon of the annealed PET sample.